Analyzing brainwaves while listening to Quranic recitation compared with listening to music based on EEG signals - Al-Galal, Sabaa Ahmed Yahya; Alshaikhli, Imad Fakhri Taha (IIUM Press, International Islamic University Malaysia, 2017)
The electroencephalogram (EEG) is an acquiring of the electrical fluctuations that occur in the brain, generated simply by positioning electrodes over the scalp with amplification of the electrical potential produced. The actual EEG indicates three primary types of wave, named alpha, beta and delta, which are distinct based on their rate of production. Data has been collected from twenty five subjects using BrainMarker EEG hardware and software. Brainwaves were measured, focusing on the Alpha and Beta bands to measure subjects’ calmness while listening to Quran recitation compared with relaxing music. The result showed that higher alpha magnitudes were generated during listening to Quran recitation.